(untitled) (Global Journal of Human-Social Science, 2011)
The basic objective of every state is to uplift social welfare of the society There are different ways to boost the process of socio -economic growth welfare and development but the role of workers remittances is not the sole but very decisive and eminent in its nature Therefore this aims to explore theoretically and empirically the impacts of workers remittances on economic growth of Azerbaijan and Armenia s economies The statistical analysis has been made through simple log linear regression model and the method of least square has been used The finding of the study indicates that worker remittances are significant and have positive impacts on economic growth and development for the study area Thus findings suggest that the relevant authorities of both the countries need to formulate appropriate conducive policies in order to encourage worker remittances In addition it is further suggests that workers remittances received from other countries must also be utilized more efficiently to have similar impacts